2020
DOI: 10.1111/sed.12748
|View full text |Cite
|
Sign up to set email alerts
|

The upper Miocene diatomaceous sediments of the northernmost Mediterranean region: A lamina‐scale investigation of an overlooked palaeoceanographic archive

Abstract: During the late Miocene the Mediterranean experienced a dramatic intensification of opaline accumulation, recorded by the deposition of diatomaceous sediments. The fine lamination of these deposits potentially records annual to sub-annual palaeoceanographic processes that occurred during a critical phase of the geodynamic evolution of the Mediterranean basin, which eventually led to the Messinian salinity crisis. The diatomaceous facies has been interpreted by previous researchers as the product of intensified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 133 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…It has been shown that tensile‐strength deriving from the close entanglement of diatom valves (Fig. 4) is able to inhibit benthic bioturbation (Kemp & Baldauf, 1993; Bodén & Backman, 1996; Pike & Kemp, 1999; Shimada et al ., 2008; Pellegrino et al ., 2020b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that tensile‐strength deriving from the close entanglement of diatom valves (Fig. 4) is able to inhibit benthic bioturbation (Kemp & Baldauf, 1993; Bodén & Backman, 1996; Pike & Kemp, 1999; Shimada et al ., 2008; Pellegrino et al ., 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, low TOC contents of the diatomaceous shales in spite of high biosiliceous productivity agree with the notion that organic matter was mostly degraded aerobically, as hypothesized for other Neogene Mediterranean (e.g. Pérez‐Folgado et al ., 2003; Pellegrino et al ., 2020a,b) and global (e.g. White et al ., 1992; Koizumi & Yamamoto, 2018) diatomaceous deposits.…”
Section: Discussionmentioning
confidence: 99%
“…The diatom assemblage of the studied gypsum samples differs from that of the pre-MSC (Pellegrino et al, 2018) diatomaceous deposits of the Mediterranean area. The latter are dominated by Thalassionema nitzschioides, which is found in biogenic laminae reflecting a relatively well-mixed water column where nutrients previously trapped at depth were reinjected into surface waters (Pellegrino et al, 2020). This diatom species is underrepresented in gypsum.…”
Section: Paleoenvironmental Implicationsmentioning
confidence: 99%